Rasio Legis Restitusi dan Kompensasi Oleh Pelaku Kekerasan Seksual Non Fisik Terhadap Anak di Bawah Umur Secara Elektronik - Fadhila, Moch. Ivan (Universitas Proklamasi 45, 2025)
Non-physical sexual violence is regulated in Law Number 12 of 2022 concerning criminal acts of sexual violence. The regulation contains unclear norms regarding objects that are then carried out through non-physical electronic media that can degrade a person's dignity and dignity so that it occurs. The aim is to study and analyze the urgency of regulating perpetrators of non-physical sexual violence committed by minors electronically and their criminal, civil, and administrative responsibilities. The method used in this study uses a normative legal research type and uses a statutory approach and a conceptual approach. The results obtained regarding the urgency of regulating perpetrators of non-physical sexual violence by children electronically are in the form of public anxiety and the absence of supervision of the handling of criminal cases of sexual violence suffered by victims, then accountability for errors that are given material or immaterial losses can be through restitution and compensation based on the conditions stipulated in the laws and regulations.